Lane detection and tracking control for unmanned aerial vehicles using image segmentation - Tan, Zhi Jie (Nanyang Technological University, 2022)
Lane detection has been widely used in land-based vehicles to carry out autonomous driving. The same concept can be applied to aerial vehicles to enable autonomous maneuvering based on the detected runway. This opens the possibilities of automated capabilities such as path tracking, automatic landing, and automatic take-off.